(3GdagQSJs - (3CHh ESMGb EHQGgje Hf gdGd Hf Ydj GdadGdj GdSLdeGSj, GHf gdGds
(3ChdgG (B:s
(3CeG HYO , aEf Gddg SHMGfg ef aVdg MaXg Ojfg abjV dMaX GdSfg hGdBKGQ cd MGaX eJjbX s
(3BNQgG (B:s
(3hgPG eG JjSQ EjQGOg gfG eeG MaX ef CSGfjOg , hYQa ef TjhNg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B454 - (3U(B507s
(3YdjgG ebGHdI SfI (B1314(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B78s
(3Odjd eDQN GdeZQH GdCbUi (B- (3U (B347 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B312 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs